2021
DOI: 10.1186/s13705-021-00291-8
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing German consumers’ willingness to pay for green electricity tariff attributes: a discrete choice experiment

Abstract: Background In order to achieve an environmentally friendly and sustainable energy supply, it is necessary that this goal is supported by society. In different countries worldwide it has been shown that one way consumers want to support the energy transition is by switching to green electricity. However, few people make the leap from their intention to a buying decision. This study explores parameters that influence whether German consumers would hypothetically decide to switch to a green electr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…But environmental concern and innovativeness were found to be having an insignificant relationship with household intention (Lan et al , 2021). Also, Danne et al (2021) concluded that consumers’ decision related to green energy adoption is significantly influenced by the source of energy, switching process and attitude towards renewable energy. The results of Issock et al (2020) indicated that customer trust is influenced by the perception of quality and price of energy efficiency technology/products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But environmental concern and innovativeness were found to be having an insignificant relationship with household intention (Lan et al , 2021). Also, Danne et al (2021) concluded that consumers’ decision related to green energy adoption is significantly influenced by the source of energy, switching process and attitude towards renewable energy. The results of Issock et al (2020) indicated that customer trust is influenced by the perception of quality and price of energy efficiency technology/products.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Thomas et al (2021) concluded that adoption decision is significantly affected by compatibility energy requirements; the cost of technology plays a significant role in adoption. There are a few other studies conducted on technical aspects, such as PV panel performance in different weathers conditions, and willingness to pay a premium for technically superior solar technologies (Bhardwaj et al , 2019; D’Alpaos and Bragolusi, 2021; Danne et al , 2021; Bright et al , 2017) .…”
Section: Introductionmentioning
confidence: 99%
“…They can be used to understand the past and present status, predict the future and support the decision making. -Internet of Things, an emerging technology that uses sensors, actuators, and communication technologies to measure and transmit data for fast and optimal decision making [24]. Energy smart meters, sensors, actuators, and sensor networks are key elements at the microenergy/household level.…”
Section: Enabling Technologiesmentioning
confidence: 99%
“…During the implementation and adaptation, ILECs must deal with technological, socio-economic, environmental, and institutional issues that can act either encouraging on such systems establishment and growth or limiting in favor of centralized systems [4]. Within the eNeuron project, 24 main key issues have been identified, among technological, socioeconomic, environmental, and institutional ones, as reported in Table V [22][23][24][25][26].…”
Section: Key Issuesmentioning
confidence: 99%
“…Discrete choice experiment (DCE) has emerged as a popular quantitative research method to study individuals' preferences for a variety of sustainabilityand energy-related technologies, services and policy measures, including contributions in this journal [33][34][35]. The basic idea of the method is that instead of revealing preferences through empirical observations, researchers have individuals' explicitly state their preferences regarding a set of predefined options.…”
Section: Discrete Choice Experiments In Energy Researchmentioning
confidence: 99%